(untitled) (Food In, 2010)
This issue contains: • A short account of anatomy and physiology of bivalve molluscs, marine gastropods, echinoderms and tunicates. • Economic importance of live bivalve molluscs . • Bacterial and viral illness associated with consumption of live bivalve molluscs. Microbiological risk management. • Marine biotoxins and chemical contaminants. • Bivalve molluscs production. • Harvesting of live bivalve molluscs and post harvest treatments. • Packaging and labelling of live bivalve molluscs, echinoderms, tunicates and marine gastropods • References. • Enclosure: identification sheets of the main commercial species of bivalve molluscs and marine gastropods.